Teachers’ authoritarian leadership and students’ well-being: the role of emotional exhaustion and narcissism - Song Peng; Yu Huang (BMC Psychology)
Abstract Background Teachers’ leadership styles have a significant impact on students’ academic performance, physical health and mental health. Authoritarian leadership, as a typical leadership style, is prevalent in the teacher community. The purpose of this study was to examine the mechanisms by which authoritarian leadership impacts students’ well-being. We also examined the mediating role of emotional exhaustion and the moderating role of narcissism. Methods This study is based on conservation of resources theory. We selected a sample of 369 students from a university in Sichuan province, collected data through two time points, and tested the data using SPSS 24.0 and AMOS 22.0. Results It was found that teachers’ authoritarian leadership negatively impacted students’ well-being and that emotional exhaustion mediated the relationship between authoritarian leadership and well-being. Narcissism not only moderated the effect of authoritarian leadership on emotional exhaustion, but also moderated the mediation role of emotional exhaustion. Conclusions Our findings enriched the research on authoritarian leadership and narcissism, and also had important practical implications for future teacher teaching in higher education.